Stakeholder-Identified Barriers, Challenges, and Obstacles in Community Gardens - Susan Webb; John M. Diaz (EDIS)
Florida Extension agents play a vital role in assisting community members to start and sustain community gardens through site visits, workshops, and educational events. This 3-page document discusses the results of a Delphi study conducted in order to create a picture of the barriers, challenges, and obstacles to starting and sustaining community gardens in Florida. Written by Susan Webb and John Diaz and published by the UF/IFAS Department of Agricultural Education and Communication, March 2018. http://edis.ifas.ufl.edu/wc301